Innovative vaginal manipulator technique vs. traditional method for vaginal fornix deployment in robotic sacrocolpopexy - Ota, Yoshiaki; Ota, Kuniaki; Takahashi, Toshifumi; Kawamura, Shogo; Shiota, Mitsuru; Shimoya, Koichiro (Frontiers in Surgery, 2024)
Introduction and hypothesisPelvic organ prolapse (POP) affects approximately 30% of middle-aged and older women, with 11%–19% requiring surgical intervention. Laparoscopic sacrocolpopexy preserves the vaginal axis and length but involves a steep learning curve and longer operation times. Robotic sacrocolpopexy (RSC) addresses these issues, offering enhanced surgical precision. This study aimed to evaluate the feasibility and effectiveness of a novel vaginal manipulator (Hoyte Sacro Tip®; Cooper Surgical, Trumbull, CT, USA) compared with the traditional spatula in RSC.MethodsThis retrospective cohort study included 88 females undergoing RSC at Kawasaki Medical School Hospital between January 2021 and December 2023. Patients were divided into two groups: spatula (n = 50) and vaginal manipulator (n = 38). Data on patient demographics, operative outcomes, and postoperative POP quantification (POP-Q) scores were collected.ResultsBaseline characteristics were similar between the groups, except for gravidity and hypertension, which were higher in the spatula group than that in the vaginal manipulator group. No significant differences were found in operative time, console time, estimated blood loss, or complication rates between the groups (p = 0.08, 0.12, 0.19, and NA, respectively). Hospital stays were shorter in the vaginal manipulator group (median 6.5 vs. 7.0 days, p = 0.03) than in the spatula group. Both groups showed improved POP-Q scores postoperatively. However, the vaginal manipulator group had significantly lower ΔC scores than that of the spatula group (6.26 ± 3.88 vs. 8.53 ± 3.25, p = 0.02).ConclusionsThe vaginal manipulator proved to be a safe and feasible alternative to the traditional spatula, with comparable perioperative outcomes and shorter hospital stays. The manipulator's design facilitated better tissue dissection, potentially improving surgical efficiency.